Customers’ purchasing risks - Плахтій, Юлія Романівна (Technology audit and production reserves, 2014)
The customers’ purchasing risks are considered in the paper. The results of the research in this field are given. The main objective of the study lies in developing the method of a quantitative assessment of such risks for the purpose of managing them. The causes and effects of purchasing defective, unsafe and faked goods by consumers are considered in the paper. The given method allows obtaining a quantitative assessment of consumer’s risk and losses from a particular type of product, taking into account its peculiarities. The research results can be used by experts in examining goods, by manufacturers and specialists in the field of consumer rights protection. Developing a system of informing people about such risks will reduce consumer’s dissatisfaction and the amount of complaints to respective authorities, and also draw manufacturers’ attention to the problem of ensuring a due product quality.